Connective Tissue Growth Factor: From Molecular Understandings to Drug Discovery - Chen, Zihao; Zhang, Ning; Chu, Hang Yin; Yu, Yuanyuan; Zhang, Zong-Kang; Zhang, Ge; Zhang, Bao-Ting (Frontiers in Cell and Developmental Biology, 2020)
Connective tissue growth factor (CTGF) is a key signaling and regulatory molecule involved in different biological processes, such as cell proliferation, angiogenesis, and wound healing, as well as multiple pathologies, such as tumor development and tissue fibrosis. Although the underlying mechanisms of CTGF remain incompletely understood, a commonly accepted theory is that the interactions between different protein domains in CTGF and other various regulatory proteins and ligands contribute to its variety of functions. Here, we highlight the structure of each domain of CTGF and its biology functions in physiological conditions. We further summarized main diseases that are deeply influenced by CTGF domains and the potential targets of these diseases. Finally, we address the advantages and disadvantages of current drugs targeting CTGF and provide the perspective for the drug discovery of the next generation of CTGF inhibitors based on aptamers.